Health, nutrition, human capital and economic growth in Colombia, 1995-2000 (2003)
Although most of the literature on economic growth has focused on studying the impact of economic growth on health status of the population, research in the last decades has given greater importance to the analysis of the impact of nutrition and health on human capital accumulation, economic growth and social development. For the specific case of Colombia, very few studies have analyzed, at the individual level, the impact of health status on labor productivity. This study expands our knowledge on the impact of health on human capital accumulation and long term economic growth. Using empirical evidence from the DHS of 1995 and 2000, it examines the relationships between health status, education and labor productivity, and it analyzes the likely impact of nutrition and health status on human capital accumulation. In addition it shows evidence of the intergenerational transmission of good nutritional status in 1995 and 2000 in Colombia.